Isolation, identification and study of the probiotic criteria of Lactobacillus plantarum isolated from the raw goat milk of the five farms of the Oran region - A. Mami; M. Djelilate; A. Kheloufi; A. Mahboubi (Algerian Journal of Research and Technology (AJRT), 2020)
Lactic acid bacteria (LAB) are widespread microorganisms which can proliferated in all dairy products. The purpose of this study is to provide an evidence of the possible probiotic existence and to access the potential of technology by depicting the main preventive and therapeutic properties of some Lactobacillus species. Around 64 strains of Lactobacillus were isolated from goat’s raw milk of Algeria. The strains which produce antimicrobial substances were detected after their exposure to the solid culture medium. Among all strains, only one strain has exposed an inhibiting activity. This one was identified to a species level by microbiological and biochemical methods. The results achieved so far showed that Lactobacillus plantarum can resist to acidic, basic and enzymatic stresses. Indeed, the former strain could be described as a probiotic. Moreover, the inhibition activity of the Lactobacillus plantarum against foodaltering strains is clearly obtained by testing these strains with direct method. Finely,our results reinforce the hypothesis that the raw goat’s milk can provides an excellent ecosystem for the development of a number of micro-flora with probiotic properties.